Evaluation of range of motion of hallux metatarsophalangeal and interphalangeal joints after periarticular osteotomies - Pereira, Nathália Christine; Maricondi Massari, Daniel; Almeida de Pousa Prieto, Thiago; Gomes Figueiredo, Márcio; Ignácio, Helencar (Journal of the Foot & Ankle, 2022)
Objective: Evaluate the impact of Chevron and extended Chevron techniques associated with Akin osteotomy on the range of motion (ROM) of hallux metatarsophalangeal joint (MPJ) and interphalangeal joint (IPJ) after three months and one year. Methods: Sixteen patients (17 feet) were evaluated for the ROM of hallux MPJ and IPJ pre-and postoperatively, the flexion-extension measurements were performed using a goniometer. Results: Comparing the pre-and postoperative measurements at three months and one year, the ROM decreased in MPJ extension and flexion, 9o and 5o, respectively, and IPJ flexion, 5o. The values presented statistical significance according to the analysis demonstrated (p>0.05). However, the decrease in IPJ extension was not statistically significant (decrease of 0.8o and p<0.05). Conclusions: Periarticular osteotomies of hallux MPJ had a significant decrease in the ROM after three months and one year. Level of Evidence II; Therapeutic Studies - Investigating the Results of Treatment; Prospective Comparative Study.